A case study on combined economic emission and load dispatch using biogeography based optimisation technique. (7th May 2021) - Goyal, Sunil Kumar; Singh, Jitendra; Saraswat, Amit; Kanwar, Neeraj; Shrivastava, Manish; Mahela, O.P.
Economic load dispatch (ELD) is economic scheduling of all generating units for variable load conditions of power system. At the same time, emission of pollutants from conventional thermal power plants need to be controlled for reducing air pollution. Therefore, optimisation of operating cost and emission of pollutants is required for the economic and safe power generation. This paper proposes optimisation of load scheduling for combined economic emission and load dispatch (CEELD) problems. Biogeography based optimisation (BBO) technique is employed to provide the lowest fuel cost at minimum emission of pollutants of all the generating units for a given load. The CEELD solution is obtained by applying BBO technique on a standard IEEE 30 bus - 6 generator system. All the parameters are evaluated in MATLAB for 50 and 100 population size at a given load. The results are compared with the existing methods to prove the efficacy of the proposed technique.